MEMPERKUAT OCB: PERAN KEPEMIMPINAN TRILOGI, KEPUASAN, DAN KOMITMEN - Yuliana, Ika; Kurniawan, Ignatius Soni (2020)
Supermarkets are expected to develop the quality of their human resources in ways that can build Organizational Citizenship Behavior (OCB). Trilogy leadership, job satisfaction and organizational commitment can be important factors that influence OCB, and this was tested in this study. Samples were taken by applying the non-probability method with saturated samples on Pamella Supermarket employees. The research findings state there is a mediation of organizational commitment to the effect of job satisfaction on OCB. Furthermore, trilogy leadership was found to have a positive effect on job satisfaction.